A Few Remarks on the Presence of Wood in Funeral Rites of the Lusatian Cultural in the Lublin Region - Kłosińska, Elżbieta Małgorzata (Analecta Archaeologica Ressoviensia, 2017)
In the Early Iron Age, there were burial cemeteries (Bliskowice, Krupy, Lublin-Jakubowice Murowane) in the Lublin region where wooden chests/sarcophagi were built, probably as family graves. These cemeteries were arranged in order: rows of graves were running along the E-W axis, and each chest was located along the S-N axis. The dead, equipped with vessels and animal food, were burnt together with the chest. This custom refers to the burial rite performed by the population of the Western-Podolian Scythian culture. Previously, in the Bronze Age, population of the Lusatian culture used wood during funerary rites, but to a lesser extent (palisades and fences).